Effects of obstructive sleep apnea on endogenous circadian rhythms assessed during relaxed wakefulness; an exploratory analysis. (2nd June 2020) - Butler, Matthew P.; Thosar, Saurabh S.; Smales, Carolina; DeYoung, Pamela N.; Wu, Huijuan; Hussain, Mohammad V.; Morimoto, Miki; Hu, Kun; Scheer, Frank A. J. L.; Shea, Steven A.
ABSTRACT: Obstructive sleep apnea (OSA) is associated with hypertension, cardiovascular disease, and a change in the 24 h pattern of adverse cardiovascular events and mortality. Adverse cardiovascular events occur more frequently in the middle of the night in people with OSA, earlier than the morning prevalence of these events in the general population. It is unknown if these changes are associated with a change in the underlying circadian rhythms, independent of behaviors such as sleep, physical activity, and meal intake. In this exploratory analysis, we studied the endogenous circadian rhythms of blood pressure, heart rate, melatonin and cortisol in 11 participants (48 ± 4 years; seven with OSA) throughout a 5 day study that was originally designed to examine circadian characteristics of obstructive apnea events. After a baseline night, participants completed 10 recurring 5 h 20 min behavioral cycles divided evenly into standardized sleep and wake periods. Blood pressure and heart rate were recorded in a relaxed semirecumbent posture 15 minutes after each scheduled wake time. Salivary melatonin and cortisol concentrations were measured at 1–1.5 h intervals during wakefulness. Mixed-model cosinor analyses were performed to determine the rhythmicity of all variables with respect to external time and separately to circadian phases (aligned to the dim light melatonin onset, DLMO). The circadian rhythm of blood pressure peaked much later in OSA compared to control participants (group × circadian phase, p < .05); there was also a trend toward a slightly delayed cortisol rhythm in the OSA group. Rhythms of heart rate and melatonin did not differ between the groups. In this exploratory analysis, OSA appears to be associated with a phase change (relative to DLMO) in the endogenous circadian rhythm of blood pressure during relaxed wakefulness, independent of common daily behaviors.